Dance expertise modulates visual sensitivity to complex biological movements. (September 2017) - Orlandi, Andrea; Zani, Alberto; Proverbio, Alice Mado
Abstract: Motor resonance processes that occur when observing an individual perform an action may be modulated by acquired visuomotor expertise. We used the event-related potential (EEG/ERP) technique to investigate the ability to automatically recognize a subtle difference between very similar novel contemporary dance movements. Twelve professional dancers and twelve non-dancers were shown 212 pairs of videos of complex whole-body movements that lasted 3 s. The second of each pair was the repetition of the previous movement or a slight variation of it (deviance). The participants were engaged in a secondary attentional task. Modulation of a larger centro-parietal N400 effect and a reduction of the Late Positivity amplitude (repetition suppression effect) were identified in response to deviant stimuli only in the dancers. Source reconstruction (swLORETA) showed activations in biological motion, body and face processing related areas, and fronto-parietal and limbic systems. The current findings provide evidence that acquired dance expertise modifies the ability to visually code whole-body complex movements. Highlights: Dancers and controls were shown novel dance moves during electroencephalography. A N400 and a reduction of Late Positivity to deviant stimuli were found in dancers. Source reconstruction showed activity in mirror system and superior temporal gyrus.